Improving the College Students’ Learning Results and Active Participations in the Elementary Social Science Subject by using Jigsaw Cooperative Learning Technique - Prihatin Sulistyowati; Denna Delawanti Chrisyarani (Pancaran Pendidikan, 2018)
This study aimed to improve the college students’ active participation and results in learning the Elementary Social Science subject by using Jigsaw cooperative learning technique and explain their responses to the implementation of the technique. This is a Classroom Action Research. The sample and population used in this study were the students in the F 2015 class who consisted of 38 students; 11 men and 29 women. The data used are observation, learning results/scores, and the students’ responses which were supported by documentation and field notes. Simple quantitative and qualitative descriptive data analysis were used in this research. The results of the study showed an increase in the participation and results, from 72.25% (27 active students) and 73.25 as the average score in Cycle 1 to 83% (32 active students) and 84.5 as the average score in Cycle 2. The students also showed a positive response to the implementation of Jigsaw cooperative learning technique.